2019
DOI: 10.1049/iet-ifs.2017.0585
|View full text |Cite
|
Sign up to set email alerts
|

Costly freeware: a systematic analysis of abuse in download portals

Abstract: Freeware is proprietary software that can be used free of charge. A popular vector for distributing freeware are download portals, i.e., websites that index, categorize, and host programs. Download portals can be abused to distribute potentially unwanted programs (PUP) and malware. The abuse can be due to PUP and malware authors uploading their ware, by benign freeware authors joining as affiliate publishers of PPI services and other affiliate programs, or by malicious download portal owners. In this work, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Although the use of digital signatures in malware is not a growing trend [6], [7], there are documented cases of signed malware samples in the wild (such as Stuxnet [8], Duqu, or Flame, to name a few). Malware developers use trusted certificates that were either compromised or issued directly to them to sign their software.…”
Section: Comité Ejecutivomentioning
confidence: 99%
“…Although the use of digital signatures in malware is not a growing trend [6], [7], there are documented cases of signed malware samples in the wild (such as Stuxnet [8], Duqu, or Flame, to name a few). Malware developers use trusted certificates that were either compromised or issued directly to them to sign their software.…”
Section: Comité Ejecutivomentioning
confidence: 99%
“…In comparison, our work measures malware distribution via multiple channels like the Play market store, alternative markets, browsers, IM, and PPI services. Prior work has analyzed Windows malware distribution through underground pay-per-install services [23], drive-by downloads [38], [58], free streaming services [59], and download portals [35], [60]. Results from these studies do not necessarily extrapolate on Android due to inherent platform differences.…”
Section: Related Workmentioning
confidence: 99%
“…Geniola et al [27] collected 800 installers of promoted applications from 8 download portals, executed them in a sandbox, and found that 1.3% of those installers drop well-known PUP to the system. Rivera et al [26] measured the amount of abuse in download portals. They analyzed all Windows programs offered by 20 download portals and reported an overall ratio of PUP and malware between 8% and 26%.…”
Section: Related Workmentioning
confidence: 99%
“…Download portals are websites that index, categorize, and host programs. Prior work from security vendors [23][24][25] and academic researchers [26,27] have studied the abuse of download portals by PUP and malware. A commercial PPI service acts as an intermediary between advertisers, who want to distribute their programs, and affiliates, who own programs (typically freeware) that users want to install.…”
Section: Introductionmentioning
confidence: 99%